2018
DOI: 10.30834/kjp.30.2.2018.47
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Inpatient Suicides: An Attempt to Portray an Approach

Abstract: IPS is the second most common sentinel event reported to the Joint Commission. Studies and statistics related to IPS are limited, as many cases are not appropriately reported, thereby masking the exact figures. Deliberate improperinadequate reporting and hiding of cases are mostly assumed to be for fear of lawsuits. 3 ABSTRACT Inpatient Suicide (IPS) is the second most common sentinel event reported to the Joint Commission. Psychiatric inpatient suicide rates in the USA, China, New Zealand, Australia, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…The epidemiological studies revealed the suicide rate in patients hospitalized in psychiatry services as 13.7 per 10000. In addition, the male-to-female ratio among psychiatric inpatients that committed suicide was reported as 2:1 (Thomas et al 2018). In a study conducted in India (Shinde et al .2014), the male-to-female ratio among psychiatric inpatients that committed suicide was 1.3 to 1.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological studies revealed the suicide rate in patients hospitalized in psychiatry services as 13.7 per 10000. In addition, the male-to-female ratio among psychiatric inpatients that committed suicide was reported as 2:1 (Thomas et al 2018). In a study conducted in India (Shinde et al .2014), the male-to-female ratio among psychiatric inpatients that committed suicide was 1.3 to 1.…”
Section: Discussionmentioning
confidence: 99%
“…In [10], the author finds that the temperature during India's main agricultural growing season has a strong positive effect on annual farmer suicide rates. In [11], the author suggests that Impatient suicides (IPS) needs early diagnosis and tolerable treatment of psychiatric disorders can prevent IPS to a great extent. In [12], the author identified that the environmental and psychological factors, are self-report measures helps in monitoring the behavior of a person.…”
Section: Literature Reviewmentioning
confidence: 99%